2010
DOI: 10.1002/pen.21785
|View full text |Cite
|
Sign up to set email alerts
|

Influence of molecular weight on rheological, thermal, and mechanical properties of PEEK

Abstract: This study focuses on the influence of molecular weight on the rheological, thermal, and mechanical behavior of poly(ether‐ether‐ketone) (PEEK), a semicrystalline high‐performance polymer. The results show that the molecular weight of PEEK has significant influence on its rheological, thermal, and mechanical behavior. It was found that PEEK has the unique characteristic of two shear‐thinning regions. The shear viscosity and the stress relaxation time of PEEK increase significantly as molecular weight increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 15 publications
6
49
0
Order By: Relevance
“…The main chain relaxation of the PEEK, taken at the maximum of tan δ, occurs at 165.5 °C, as shown in Figure 3, similar to values reported in the literature 6,11,16 . This high relaxation temperature for the PEEK polymeric structure is associated with the rigid segments of its backbone, as reported by Yuan et al 16 and White et al 20 .…”
Section: Dynamic Mechanical Thermal Propertiessupporting
confidence: 72%
See 3 more Smart Citations
“…The main chain relaxation of the PEEK, taken at the maximum of tan δ, occurs at 165.5 °C, as shown in Figure 3, similar to values reported in the literature 6,11,16 . This high relaxation temperature for the PEEK polymeric structure is associated with the rigid segments of its backbone, as reported by Yuan et al 16 and White et al 20 .…”
Section: Dynamic Mechanical Thermal Propertiessupporting
confidence: 72%
“…This high relaxation temperature for the PEEK polymeric structure is associated with the rigid segments of its backbone, as reported by Yuan et al 16 and White et al 20 . On the other hand, the flexible chains of the PA-11 can explain its T g value of 13.6 °C (Figure 3), similar to values reported by Chaupart and Serpe 23 , and is associated with the long segments between the amide groups and the significant amount of plasticizer present in this particular grade.…”
Section: Dynamic Mechanical Thermal Propertiessupporting
confidence: 50%
See 2 more Smart Citations
“…That would mean the Rouse time of the longest chains is τ R = 0.17 s and, combined with their reptation time of τ d ≈ 10 s, suggests that those longest chains have M/M e = τ d /6τ R = 10 entanglements. Yuan et al (2011) reported two distinct shear thinning regions in the flow curves of different grades of PEEK at 380°C…”
mentioning
confidence: 97%